2020
DOI: 10.1186/s13046-020-01590-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing against COVID-19: focus on anticancer agents

Abstract: Background: The very limited time allowed to face the COVID-19 pandemic poses a pressing challenge to find proper therapeutic approaches. However, synthesis and full investigation from preclinical studies to phase III trials of new medications is a time-consuming procedure, and not viable in a global emergency, such as the one we are facing. Main Body: Drug repurposing/repositioning, a strategy effectively employed in cancer treatment, can represent a valid alternative. Most drugs considered for repurposing/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 104 publications
0
57
0
Order By: Relevance
“…It is particularly noteworthy to mention that part of the most signi cantly predicted pathways targeted by the six microRNAs, were related to respiratory virus infections (e.g., In uenza A) and other viral infections (e.g., Herpes Simplex). The observed microRNA-induced modulation of TMPRSS2 provides new insights for potential assessment of agents capable of regulating the microRNA expression and induces TMPRSS2 downregulation, as SARS-CoV-2 infection prevention strategy [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…It is particularly noteworthy to mention that part of the most signi cantly predicted pathways targeted by the six microRNAs, were related to respiratory virus infections (e.g., In uenza A) and other viral infections (e.g., Herpes Simplex). The observed microRNA-induced modulation of TMPRSS2 provides new insights for potential assessment of agents capable of regulating the microRNA expression and induces TMPRSS2 downregulation, as SARS-CoV-2 infection prevention strategy [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…Several of the other cancer associated genes (GSTA1, ABCG2, CAT, CTSD, TF, EGR1, TNFSF10) appeared in the network (Figure 2c-d) were linked with transcriptional response to SARS-CoV-2 infected cell lines affecting innate immunity (CHRNB4, CAT, CTSD, IFNB1), and endothelial and vascular in ammation (TNF, ICAM) in COVID-19. These DEGs altogether displayed association with old and new drugs potentially useful in COVID-19 therapy and tested or used in the oncological settings as well (Ciliberto et al, 2020), including rapamycin, chloroquine, lopinavir, ritonavir, ribavirin as appeared in PDI network in our study (Figure 6), remdesivir, tocilizumab and sarilumab as shown in virus-human protein interaction (Figure 1). The PDI network of group A genes showed top scores of 0.985 and 0.923 for rapamycin (degree of interaction: 5) with IL10, IL2A, CD8A, CD40LG, and CSF3 (Figure 6a).…”
Section: Resultsmentioning
confidence: 57%
“…Drug repositioning is a novel attractive strategy used for nding new anticancer agents because it could lower the cost of developing new drugs and introduce them into the market quickly [42,43]. This strategy has also been applied to nd therapeutic agents against coronavirus disease 2019 in the midst of a global emergency when there is no time to conduct phase-III trials [44]. Because HMG-CoA reductase inhibitors have various physiological properties such as regulating metabolisms [45,46], inhibiting in ammation [47,48], modulating the immune system [49], and inhibiting cancer growth [12-14, 50, 51], they are one of the most potent candidate drugs to be used for purposes other than currently approved ones.…”
Section: Discussionmentioning
confidence: 99%